THE ROLE OF EMOTIONAL APPEAL IN MODERN ADVERTISING: A STUDY ON ROLE OF E-ADVERTISEMENT ON CONSUMER BUYING BEHAVIOUR - Bhargavi, L Manju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study delves into the significant role of emotional appeal in modern advertising, exploring its psychological underpinnings and effectiveness in influencing consumer behaviour. The research examines how emotions are strategically used to connect with audiences, build brand loyalty, and drive purchase decisions. Through a comprehensive review of literature and case studies, the study highlights the psychological mechanisms that make emotional appeal a powerful tool in advertising. The findings suggest that emotional appeal not only enhances brand recall but also fosters long-term consumer relationships, making it a critical component of successful advertising campaigns. The digital revolution has fundamentally transformed the landscape of advertising, giving rise to e-advertisement as a powerful tool for influencing consumer buying behavior. This study investigates the role of e-advertisement in shaping consumer decisions, focusing on the elements that make digital ads effective, such as personalization, interactivity, and data-driven targeting. By analyzing consumer responses to various forms of e-advertisement, including social media ads, search engine marketing, and email campaigns, the research seeks to uncover the underlying psychological mechanisms that drive consumer engagement and purchasing decisions. The study also explores the challenges associated with e-advertising, including ad fatigue, privacy concerns, and the growing prevalence of ad-blocking software. Through a combination of qualitative and quantitative methods, the research aims to provide a comprehensive understanding of how e-advertisements influence consumer behavior, as well as strategies for enhancing their effectiveness in a competitive digital marketplace. The findings of this study will offer valuable insights for marketers and advertisers seeking to optimize their e-advertising strategies and build stronger connections with consumers in the digital age.